Analisis Penerapan Akuntansi Berbasis Akrual atas Pendapatan menurut Undang-Undang Perpajakan pada PT. Merapi Utama Pharma Medan - Suci Chairani, Tantry; Anwar Pulungan, Khairul (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of writing this thesis is to examine the application of accrual-based accounting to income carried out by PT. Merapi Utama Pharma Medan, in accordance with applicable laws and regulations. This research uses descriptive analysis methodology. The methodology used in this research involves the use of descriptive statistical analysis for data analysis purposes. The second category of data used in this research consists of information originating from official company documents. Data collection methods used in this research include interviews, surveys, and examination of financial records and other related documents. This research tests and evaluates the implementation of income accrual accounting in accordance with Indonesian laws and regulations (Tax Law) at PT. Merapi Utama Pharmacy, Medan. This research is supported by the use of accessible data, allowing the author to obtain important findings. Company PT. Merapi Utama Pharma Medan has not fully implemented payroll accounting practices in accordance with the requirements and deadlines specified in the relevant tax regulations. Reconciliation reports are generated due to differences in the accounting treatment of income and expenses between the two systems. Financial reconciliation can be classified into two categories based on their duration: permanent and temporary. Financial statements are needed to reconcile the difference between positive and negative cash flow variances. Differences in taxable income can be caused by the recognition of certain expenses in the tax records which are not considered as such in the financial records; These expenses have the capacity to reduce an organization's taxable income.